THE TECHNOLOGY OF TEACHING ENGLISH GRAMMAR TO 10-11 GRADES OF SECONDARY SCHOOLS BASED ON A COMMUNICATIVE APPROACH - Odilbek Usmonjonov (Galaxy International Interdisciplinary Research Journal, 2023)
This article reflects on the technology of teaching English grammar on the basis of a communicative approach to students in grades 10-11 of secondary schools. In the ever-evolving landscape of education, the integration of technology has become imperative for effective teaching and learning. This is especially true when it comes to the teaching of English grammar, a subject that often requires innovative approaches to engage students. In grades 10-11 of secondary schools, where students are at a crucial stage of language development, the communicative approach coupled with technology proves to be a potent combination. English grammar instruction often leaned heavily on rote memorization and discrete rule learning.